2014
DOI: 10.15406/jnsk.2014.01.00024
|View full text |Cite
|
Sign up to set email alerts
|

Are Multiple Intracranial Aneurysms, More Than 5 At One Time, Almost Exclusively A Female Disease? A Clinical Series and Literature Review

Abstract: IntroductionMultiple intracranial aneurysms (MIAs) were first described by Thomson [1] in 1842. Since that time, a female predisposition for the disease has been widely recognized [2][3][4][5][6][7][8][9][10]. Multiple intracranial aneurysms (IAs) occur in approximately one-fourth to one-third of all ruptured and unruptured aneurysm patients. The female to male ratio shows a predisposition for the female gender, with almost exclusively a female predominance when more than 5 aneurysms are present at one time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…In our series, female/male ratio was 2.2/1 with a female dominance similar to the literature (11)(12)(13). Defillo et al reported a 1.39-fold increased incidence of MIA in females (14). In the study of Inagawa including 126 cases, 69% of MIA cases were females (15).…”
Section: Discussionsupporting
confidence: 88%
“…In our series, female/male ratio was 2.2/1 with a female dominance similar to the literature (11)(12)(13). Defillo et al reported a 1.39-fold increased incidence of MIA in females (14). In the study of Inagawa including 126 cases, 69% of MIA cases were females (15).…”
Section: Discussionsupporting
confidence: 88%
“…A preponderance of intracranial aneurysms occurs in women, which increases with the number of aneurysms (Defillo et al, 2014). In samples of people aged 50 and over, this preponderance may approach a ratio of 1:2, or even greater.…”
mentioning
confidence: 99%